2019
DOI: 10.1002/mdc3.12881
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Salivary Glands for Botulinum Toxin Treatment: Ultrasound Versus Landmark Guidance

Abstract: Background Background: Sialorrhea is a troublesome symptom in a variety of neurological diseases. Recently, local injection of botulinum toxin into the salivary glands was approved for treatment of sialorrhea, and injection guidance by anatomical landmarks was suggested. Objective Objective: To compare the accuracy of ultrasound versus previously proposed anatomical landmarks for localizing the salivary glands. Methods Methods: In a cross-sectional study in 21 adults, landmark positions (LM) of the parotid gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
0
17
0
8
Order By: Relevance
“…A post-mortem study showed an almost doubled hit-rate of ultrasound-guided injections in the submandibular glands compared to free-hand injections [12]. The high error-rate even of experienced injectors might be attributable to the variance of submandibular gland size as well as to different inter-and intra-individual distances between gland and mandible [1,13].…”
Section: Discussionmentioning
confidence: 99%
“…A post-mortem study showed an almost doubled hit-rate of ultrasound-guided injections in the submandibular glands compared to free-hand injections [12]. The high error-rate even of experienced injectors might be attributable to the variance of submandibular gland size as well as to different inter-and intra-individual distances between gland and mandible [1,13].…”
Section: Discussionmentioning
confidence: 99%
“…parotis ist gering. Unserer Erfahrung nach deckt sich der empfohlene Injektionspunkt nach Landmarken [100][101][102] mit dem sonographisch bestimmten Ort für die Gl. parotis recht gut.…”
Section: Injektionstechnik Zur Applikation Von Botulinumtoxin In Die ...unclassified
“…Sonographic control of injections is useful, especially when treating the submandibular salivary gland [16,20,21], as swallowing disorders caused by unintentional diffusion into the muscles of the oral floor can be avoided [9]. Numerous studies conducted in adult and pediatric patients with sialorrhea of various etiologies have confirmed that BoNT/A injections (abobotulinumtoxinA, incobotulinumtoxinA, and onabotulinumtoxinA) effectively reduce salivary secretion for periods of up to 3-4 months [1,22].…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…Although BoNT/A is more complicated to administer than anticholinergic drugs, in a vulnerable group of patients sensitive to the adverse effects of anticholinergics, the purely local effect and the excellent safety profile outweigh the challenges of the injection procedure. In our opinion, injection of BoNT/A is best achieved using ultrasound to guide needle insertion, a strategy that minimizes the risk of unnecessary adverse events [16,21] (Figure 3). We also suggest initiating a fixed injection schedule every 4 months or more, rather than treating patients when sialorrhea returns.…”
Section: Expert Opinionmentioning
confidence: 99%